2016
DOI: 10.1111/spol.12185
|View full text |Cite
|
Sign up to set email alerts
|

From Social Instrument to Migration Management Tool: Assisted Voluntary Return Programmes – The Case of Belgium

Abstract: The return of migrants to their country of origin and the development of efficient return measures have become more prominent on the political agenda of many Western European countries. Since policymakers prefer ‘voluntary’ return, governmental programmes to support the return of migrants – Assisted Voluntary Return (AVR) programmes – were developed as far back as the 1970s and have played an increasingly important role in migration policy over the last three decades. At the same time, general migration policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 44 publications
0
27
0
1
Order By: Relevance
“…Adjustment is linked to several outcomes that are of relevance for organizations, while it is also valued on its own. In addition, repatriates’ self‐concept or more specifically their cultural or international identity and sense of belonging is increasingly recognized as being an important factor associated with their adjustment (Lietaert, ; Chiang et al., ) Accordingly, literature on repatriates takes into account that international mobility can result in profound personal transformations, which might consequently influence psychological comfort on re‐entry.…”
Section: Discussionmentioning
confidence: 99%
“…Adjustment is linked to several outcomes that are of relevance for organizations, while it is also valued on its own. In addition, repatriates’ self‐concept or more specifically their cultural or international identity and sense of belonging is increasingly recognized as being an important factor associated with their adjustment (Lietaert, ; Chiang et al., ) Accordingly, literature on repatriates takes into account that international mobility can result in profound personal transformations, which might consequently influence psychological comfort on re‐entry.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the inherent difficulty of the theme of return migration, for the Belgian social workers this struggle mainly related to the element of working with migrants without legal citizenship, the limited choices they have, and the elements of force within return decisions arising from the migration management goals linked to the AVRR program (Lietaert et al, 2016b). Research already indicated that social workers are often caught between the requirements and eligibility criteria for social support related to a client's residence status and professional ethics that require support to be given to people in need, needs that are often caused by a lack of residence documents and/or (full) citizenship (Cuadra & Staaf, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This paper studies the implementation of AVRR support in Belgium. In this context, the AVRR program is strongly institutionalized, and many social workers are involved in its implementation (Lietaert, Broekaert, & Derluyn, 2016b). Therefore, the Belgian AVRR program presents one of the sole forms of institutionalized transnational social work.…”
Section: Social Work and Migration: The Transnational Perspectivementioning
confidence: 99%
See 2 more Smart Citations